In Focus/Case Study-A Responsible Company That's Making the Grade - Ireland, John; Ireland, John (Center for Creative Leadership, 2007)
Businesses that adopt corporate social responsibility consider themselves to be full partners in their communities rather than focusing solely on earning profits for their shareholders. The World Business Council for Sustainable Development defines corporate social responsibility (CSR) as "the continuing commitment by business to behave ethically and contribute to economic development while improving the quality of life of the workforce and their families as well as of the local community and society at large."